Investigating disruption : a literature review of core concepts of disruptive innovation theory - Stine Schmieg Lundgaard; Claus Andreas Foss Rosenstand (Investigating disruption : a literature review of core concepts of disruptive innovation theory, 2019)
When companies fail, several reasons (some more likely than others) can be turned to in order to explain why. Managers look for these typically interrelated networks of reasons in attempts to secure themselves and future companies from the same failure happening again. This necessitates knowledge, which, based on past experience, provides forecasts and is operational at an early stage. One reason behind company failures has been termed The Innovator's Dilemma by Clayton M. Christensen. Christensen's influential book of the same title and subject has founded a direction within innovation management that, through recent years, is gaining increasing amounts of attention. Lundgaard and Rosenstand advocate that in operationalising theory of disruptive innovation, a common understanding of its most obvious limits and potentials must be achieved. This entails a review and reflections on what the theory initially was, how it has developed, and what is has become. Furthermore, this stance entails a look into the broader context of the theory so as to not diminish its value through simplification. These two aspects are the core of the book. The authors' literature investigation draws upon a deep selection of literature specifically concerning disruptive innovation so as to provide researchers, students, and managers with an overview of the specific area. Further reading into organizational design, culture, and management is encouraged in order to fully understand the complex reality of disruptive innovation for organizations.4221 Zusammenfassung in englischer Sprache